Hydrochoerus hydrochaeris: ECOLOGY AND THE SPECIES POTENTIAL FOR PRODUCTION- A REVIEW - FELIX, Gisele A.; ALMEIDA PAZ, Ibiara C. L.; NÄÄS, Irenilza A.; GARCIA, Rodrigo G.; MOI, Marta; CALDARA, Fabiana R.; SANTI, Francielen M.; Costa JUNIOR, Rômulo G. (Revista Brasileira de Engenharia de Biossistemas, 2011)
The capibara (Hydrochoerus hydrochaeris), the largest exiting rodent is considered a wild animal of economic value. However, in Brazil legal restrictions do not allow the development of management systems of the wild free population. Outside Brazil there is the example of Venezuela, where the sustainable production of wild population is used applying the controlled hunting, which is a feasible solution for controlling the population of this rodent besides being a new source of income for the population. This review was prepared with the objective of discussing about the ecology of the species, and to present the importance for animal production, meat consumption patterns, and consumer market.